Inpatient hospital burden of hepatitis C‐diagnosed patients with decompensated cirrhosis. (19th January 2018) - McDonald, Scott A.; Innes, Hamish A.; Aspinall, Esther J.; Hayes, Peter C.; Alavi, Maryam; Valerio, Heather; Goldberg, David J.; Hutchinson, Sharon J.
Abstract: Background & Aims: To describe the burden on inpatient hospital resources over time from patients diagnosed with hepatitis C virus (HCV) infection and who have reached the decompensated stage of cirrhosis (DC), as existing estimates of hospital stay in these patients are limited. Methods: A retrospective longitudinal dataset was formed via record‐linkage between the national HCV diagnosis database and inpatient/daycase hospitalisation and death registers in Scotland. The study population consisted of HCV‐diagnosed patients with a first DC admission in 1996‐2013, with follow‐up available until 31 May 2014. We investigated and quantified the mean cumulative length of hospital stay, distributions over discharge diagnosis categories, and trends in admission rates. Results: Among our study population (n = 1543), we identified 10 179 admissions with any diagnosis post‐first DC admission. Between 1996 and 2013 there was a 16‐fold rise in annual total admissions (from 112 to 1791) and an 11‐fold rise in hospital stay (719‐8045). When restricting minimum possible follow‐up to 2 years, DC patients (n = 1312) had an overall admission rate of 7.3 per person‐year, and spent on average 43 days (26 days during first 6 months) in hospital; for all liver‐related, liver‐related other than HCC/DC, and non‐liver related only admissions, this was 39, 14, and 5 days respectively. Conclusions: HCV‐infected DC patients impose a considerable inpatient hospital burden, mostly from DC‐ and other liver‐related admissions, but also from admissions associated with non‐liver comorbidities. Estimates will be useful for monitoring the impact of prevention and treatment, and for computing the cost‐effectiveness of new therapies.